The Effect of Sustainable Livelihood Assets on the Soil and Water Conservation Level Adoption In Sumber Brantas Village, Indonesia - Warokka, Frania Yelfina Mariani; Suhartini, Suhartini; Nugroho, Tri Wahyu (Universitas Panji Sakti, 2024)
Soil and Water Conservation (SWC) plays an important role in addressing environmental problems. This research is located in Sumber Brantas Village which is a watershed of Brantas river and has potential as farming land for horticultural crops, especially vegetables besides horticultural crops also have productivity figures that consistently always go up, agricultural land in Sumber Brantas Village is 60% mostly sloping land with steep slopes more than 30 degrees which is recommended to implement conservation farming to preserve the environment. This study aims to analyze the influence of livelihood assets on the level of SWC adoption. This research was conducted from December 2022 to February 2024 and used 86 horticulture farmers as a sample calculated by slovin formula and simple random sampling method. This research method used is Tobit regression or often referred to as censored regression; this is because the dependent variable has an upper limit and a lower limit, the software used in this study is Stata 14. The results of this study show that natural capital, social capital, financial capital and physical capital significantly influence the level of adoption of soil and water conservation farming systems.